SLOPE STABILITY ANALYSIS OF THE BOZSHAKOL OPEN PIT MINE USING THE FINITE ELEMENT METHOD - Maratov, Torekeldi (School of Mining and Geosciences, 2023)
Slope stability analysis is a key part of every geotechnical problem of various extents. Ensuring an appropriate analysis enables sustained production and a safe environment at the mine site. In regard with the thesis research, a two-dimensional finite element method is selected for the analysis of the Bozshakol open-pit mine. In the process, all production stages are analyzed using numerical calculations. Particularly, the south wall of the pit is most concerning, as it appears to be the critical zone susceptible to possible instabilities based on the compiled data. Initially, the results of mining activities include uplift from the pit bottom and downslides of rock from the lateral walls of the pit section (e.g., excavation, blasting, benching). The numbers and visuals show that this pattern is prevalent throughout the production phases. Most importantly, higher displacements and deformations are observed along the south wall of the pit than along the north wall. With the critical SRF, as in production stage 2, the south wall moved as much as 0.035 m, while the north wall moved as little as 0.008 m. The rock movement was found to be 3.26 m as SRF was increased to a maximum of 2.6. This pattern necessitates keeping SRF and FoS values around or below the crucial value (2.15-2.21). In addition, as the production stages advance, we expect the maximum rock movement to increase from 0.035 to 0.142 meters from stage 2 to stage 6 if critical FoS are kept. Since total displacement fields grow proportionally as mining progresses, it is crucial to deal with potential problems as soon as they arise. Ultimately, the location of gabbro is indicative of the most active zone of displacement. As a result, this points to flaws in the rock influencing this result, which are the low intact rock and rock mass properties. Further three-dimensional research and improved sensitivity analysis are recommended for the advancement of the project.
Keywords: Type of access: Open Access; Bozshakol; mine